Mortality in Spain in the Context of the Economic Crisis and Austerity Policies - Regidor, Enrique (Am J Public Health, 2019)
Objectives. To analyze the mortality trend in Spain before, during, and after the economic crisis and austerity policies. Methods. We calculated age-standardized annual mortality rates in 2001 through 2016 and estimated linear trends in mortality rates during 4 periods (2001–2007, 2008–2010, 2011–2013, and 2014–2016) using the annual percentage change (APC). Results. All-cause mortality rate decreased during the period 2001 to 2016, although we found increases over the previous year. After adjusting for increased influenza activity (P = .743) and heat waves (P = .473), we found the greatest declines during the economic crisis (2008–2010) and the smallest in the period 2014 to 2016, in which the APC in mortality rates was −2.9 and −0.6, respectively. The APC before the crisis (2001–2007) and during austerity (2011–2013) was −2.0 and −2.2, respectively. We observed similar results in mortality from cardiovascular, respiratory, and digestive diseases and motor vehicle accidents. Mortality from cancer showed the smallest decline during the crisis and the austerity period, whereas suicide increased in the period 2011 to 2013. Conclusions. Lifestyle changes could explain the decline in mortality during the economic crisis. Increased influenza activity and the 2015 heat wave may prevent identifying a possible delayed effect of austerity policies in the slowing down of mortality decline in the period 2014 to 2016.